Nias Dance Encyclopedia as a Source of the Working Process - Tuti Rahayu Sibuea; Wiflihani (Britain International of Linguistics Arts and Education (BIoLAE) Journal, 2022)
This study aims to develop an encyclopedia on the concept of traditional dances from Nias ethnic groups in North Sumatra as a source of learning in the process of creating. This research is directed at a reference book product in the form of an encyclopedia. From this research process, the results of the development of a reference book for the local traditional dance of Nias, North Sumatra emerged. This research uses research and development (Research and Development or R&D) methods. The location or place in this study was carried out in the cities of Medan and Nias with data collection techniques obtained through observation, in-depth interviews and documentation. After all the required data have been completed, the next step is to analyze the data using a qualitative paradigm using project based research, which is obtained through data reduction,The average value obtained during the material expert feasibility test was 4.75 with a very good category and no revision. The average value obtained at the time of this media feasibility test was 4.375 with a very good category.The results of the development of this Nias traditional dance encyclopedia book can be used as a reference for students and the community as a source of the creative process for Nias traditional dances.